2010
DOI: 10.1002/jbmr.116
|View full text |Cite|
|
Sign up to set email alerts
|

Adiponectin and its association with bone mass accrual in childhood

Abstract: Circulating adiponectin levels are inversely related to bone mineral density (BMD) in humans and animal models. Previous studies in humans have been confined largely to adult populations, and whether adiponectin influences bone mass accrual in childhood is unclear. We examined this question using the Avon Longitudinal Study of Parents and Children (ALSPAC) birth cohort by investigating relationships between circulating adiponectin levels at a mean age of 9.9 years, indices of bone mass as measured by total-bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 36 publications
3
47
0
Order By: Relevance
“…Although positive relationships between fat mass and bone parameters could reflect a response to greater mechanical strain caused by greater weight, we previously observed fat mass to be positively related to upper limb bone mass, suggesting a role of metabolic pathways independently of body weight . In terms of metabolic pathways which might mediate positive influences of fat mass on bone accrual, we previously found that whereas fat mass is inversely related to adiponectin levels, the latter is inversely related to cortical bone size …”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Although positive relationships between fat mass and bone parameters could reflect a response to greater mechanical strain caused by greater weight, we previously observed fat mass to be positively related to upper limb bone mass, suggesting a role of metabolic pathways independently of body weight . In terms of metabolic pathways which might mediate positive influences of fat mass on bone accrual, we previously found that whereas fat mass is inversely related to adiponectin levels, the latter is inversely related to cortical bone size …”
Section: Introductionmentioning
confidence: 87%
“…Periosteal circumference (PC), endosteal circumference (EC) and cortical thickness (CT) were derived using a circular ring model as described in the Stratec user manual. Cortical bone was defined using a threshold above 650 mg/cm 3 and BMD C subsequently derived . Strength strain index (SSI) was calculated according to the formula published by Hasegawa and colleagues .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown high, normal, or low levels in patients with AN [101103], and one study showed an inverse association between adiponectin values and bone density parameters in adolescents with AN [104]. Adiponectin levels are inversely associated with BMD in children and adults [95, 100, 105, 106].…”
Section: Adipokinesmentioning
confidence: 99%
“…In addition, stimulation of the Y2 receptor by PYY (a hormone secreted by the L-cells of the distal gut that suppresses hunger) is believed to be deleterious to bone, based on the Y2 receptor knock-out mouse having increased bone mass associated with increased bone formation [65, 66]. Data regarding the relationship between adiponectin (another adipose-derived peptide) and BMD in childhood, adolescence, and young adulthood have been mixed [65, 67, 68], with in vitro and animal data indicating an increase in both osteoblastic and osteoclastic activity with adiponectin [69, 70]. Finally, high cortisol levels are deleterious to bone at multiple levels, and may increase in conditions of energy deficit [71].…”
Section: Hormones That Influence Bone Accrualmentioning
confidence: 99%